Distal radius morphometry of Indonesian population (Faculty of Medicine Universitas Indonesia, 2013)
Background: Distal radius morphometry (radial inclination, palmar tilt, radial height, and ulnar variance) is an important parameter in the evaluation and treatment of distal radius fractures in which anatomical alignment must be corrected. Currently, treatment of distal radius fractures in Indonesia is still based on morphometry of western population or from the contralateral side. The aim of this study is to determine distal radius morphometry of Indonesian population and to compare between right and left side, male and female gender. Methods: Distal radius morphometry was measured from 400 plain X-ray of right and left wrist AP and lateral projection. Samples were taken consecutively in Moh. Ridwan Meuraksa Army Hospital, Jakarta, from June to September 2010. Radial inclination, palmar tilt, radial height, and ulnar variance was measured. Data were recorded using tables and grouped between male and female, right and left side, statistical analysis was performed using Mann-Whitney test. Results: From 400 plain X-ray evaluated, there were 300 males and 100 females with the mean age of 25.5 years old (18-48). The mean of radial inclination was 23.99 ± 3.75°, palmar tilt 13.76 ± 4.36°, radial height 11.31 ± 1.66 mm, and ulnar variance -0.45 ± 2.03 mm. There were statistically significant differences between right and left side of radial inclination, palmar tilt, radial height, and ulnar variance. There was also statistically significant difference between male and female. Conclusion: Distal radius morphometry in Indonesian population may provide valuable data for the treatment of distal radius fractures. The use of contralateral side as reference should be reconsidered.